An Approach for Geostationary Satellite Mode Management. Issue 1 (July 2017) - Tipaldi, Massimo; Witzmann, Marco; Ferraguto, Massimo; Glielmo, Luigi
Abstract: In each mission phase, a satellite is characterized by a well-defined set of modes. They define a clear configuration of the spacecraft subsystems and have specific operational implications. In this paper, we present an approach for geostationary earth observation satellite mode management during both the Launch and Early Orbit phase and the full operational phase. It draws on a real space mission project currently carried out at OHB System AG. The configurations of the Attitude and Orbit Control System are also analyzed, their operational meaning and the relationship with the satellite modes. It is also explained how on-board autonomy requirements play a relevant role in the satellite mode definition and management. Geostationary satellites can usually be operated in a quasi real-time fashion, therefore a limited level of on-board autonomy can be sufficient. However, they can be characterized by high availability requirements and have a need for ground operation reduction, which can lead to an increased level of on-board autonomy in satellite mode management.